Melanocortin Systems on Pigment Dispersion in Fish Chromatophores - Kobayashi, Yuki; Mizusawa, Kanta; Saito, Yumiko; Takahashi, Akiyoshi (Frontiers in Endocrinology, 2012)
Alpha-Melanocyte-stimulating hormone (alpha-MSH) is responsible for pigment dispersion in the chromatophores of fish and other tetrapods such as amphibians and reptiles. Recently, we discovered that alpha-MSH did not always stimulate pigment dispersion because this hormonal peptide exerted no effects on the melanophores of flounders. We assumed that the reduction of alpha-MSH activity was related to the co-expression of different alpha-MSH receptor subtypes—termed melanocortin receptors (MCR)—a member of G-protein-coupled receptors (GPCR)—based on several reports demonstrating that GPCR forms heterodimers with various properties that are distinct from those of the corresponding monomers. In this review, we summarize the relationships between the pigment-dispersing activity of alpha-MSH-related peptides, molecular forms of alpha-MSH-related peptides, and Mcr subtypes expressed in fish chromatophores.